2020
DOI: 10.3892/ol.2020.11870
|View full text |Cite
|
Sign up to set email alerts
|

Beclin‑1 expression is associated with prognosis in a Bcl‑2‑dependent manner in non‑small cell lung cancer

Abstract: Beclin-1 and Bcl-2 expression abnormalities have been confirmed in different types of cancer. As important regulators of autophagy and apoptosis, respectively, these molecules serve a complex role in tumorigenesis. However, limited information is currently available regarding the association between Beclin-1 and Bcl-2 in (NSCLC). In the present study, the expression levels of Beclin-1 and Bcl-2 were detected in lung cancer tissues, and their prognostic significance was analyzed for NSCLC. A total of 120 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It was demonstrated that ruxolitinib partly suppressed CRC cell proliferation by inducing apoptosis through activating the intrinsic pathway. Bcl-2 family proteins that are key mediators of the intrinsic apoptosis pathway were screened out ( 25 , 26 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that ruxolitinib partly suppressed CRC cell proliferation by inducing apoptosis through activating the intrinsic pathway. Bcl-2 family proteins that are key mediators of the intrinsic apoptosis pathway were screened out ( 25 , 26 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 2,000 cells/well were plated in 96-well plates and incubated for 24 h and then exposed to gradually increasing concentrations (0, 2. 5,5,10,15,20,25,30,40, 50 µM) of ruxolitinib for 48 h. MTT solution (prepared in serum-free growth medium) was added to each well and was incubated for another 4 h at 37˚C. DMSO was added and the absorbance at 570 nm was determined using a microplate reader.…”
Section: Reagentsmentioning
confidence: 99%
“…Furthermore, a systematic review and meta-study of p62/SQSTM1 in lung cancer patients found that overexpression of p62 was linked to overall survival in lung cancer patients [37,38]. Beclin-1 expression was negatively correlated with tumor size and tumor stage of lung adenocarcinoma, and Beclin-1 expression was decreased in NSCLC tissues compared with normal tissues [39].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is involved in cancer cell metastasis by regulating EMT. The autophagy protein Beclin1 is a key regulator of tumorigenesis and metastasis in NSCLC cells, and the expression levels of Beclin1 have been shown to be significantly reduced in NSCLC tissues ( 69 , 70 ). Low Beclin1 expression levels have also been observed in patients with NSCLC with more advanced stages of cancer, increased lymph node metastasis and more poorly differentiated tumors ( 70 ).…”
Section: The Role Of Pcd In the Metastasis Of Nsclcmentioning
confidence: 99%
“…The autophagy protein Beclin1 is a key regulator of tumorigenesis and metastasis in NSCLC cells, and the expression levels of Beclin1 have been shown to be significantly reduced in NSCLC tissues ( 69 , 70 ). Low Beclin1 expression levels have also been observed in patients with NSCLC with more advanced stages of cancer, increased lymph node metastasis and more poorly differentiated tumors ( 70 ). Reduced Beclin1 expression has also been associated with shorter survival of patients with NSCLC, thus suggesting that autophagy, which is an independent prognostic indicator for the survival of patients with NSCLC, may be suppressed in these patients ( 69 ).…”
Section: The Role Of Pcd In the Metastasis Of Nsclcmentioning
confidence: 99%